A century of struggle: Afghanistan’s media development under monarchies - Pamirzad, Qurban Hussain (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2024)
This paper has used a series of historical sources, mainly in the Persian language, to explore the one-century history of Afghanistan’s media. The country has 150 years of media history, of which a century occurred during the monarchy's political system. This study explains the chronological order and structure of the media from the first newspaper, Shams-u-Nahar, which was founded in 1873 during the reign of Amir Shir Ali Khan. In addition to explaining the press's role in the war for the independence of Afghanistan, it also explores the media’s situation during King Zaher Shah’s (1933-1973) reign, when a diverse media environment emerged; simultaneously, systematic political repression was carried out and derailed the achievements. This comprehensive centenary review of Afghanistan’s media history fills the research gap about Afghanistan's media, which has only been accessible to readers and researchers in the Persian language so far. Hence, this paper will be the first of its kind to cover this era in detail, address this research void, and pave the way for researchers to learn more about Afghanistan's media history.*****Makalah ini menggunakan serangkaian sumber sejarah, terutama dalam bahasa Persia, untuk mengeksplorasi sejarah satu abad media Afghanistan. Negara ini memiliki sejarah media selama 150 tahun, dan satu abad di antaranya terjadi pada masa sistem politik monarki. Kajian ini menjelaskan urutan kronologis dan struktur media dari surat kabar pertama, Shams-u-Nahar, yang didirikan pada tahun 1873 pada masa pemerintahan Amir Shir Ali Khan. Selain menjelaskan peran pers dalam perang kemerdekaan Afghanistan, artikel ini juga mengeksplorasi situasi media pada masa pemerintahan Raja Zaher Shah (1933-1973), ketika lingkungan media yang beragam muncul; secara bersamaan, represi politik sistematis dilakukan dan menggagalkan pencapaian. Tinjauan komprehensif sejarah media Afganistan yang berusia seratus tahun ini mengisi kesenjangan penelitian tentang media Afganistan, yang sejauh ini hanya dapat diakses oleh pembaca dan peneliti dalam bahasa Persia. Oleh karena itu, makalah ini akan menjadi makalah pertama yang membahas era ini secara rinci, mengatasi kekosongan penelitian, dan membuka jalan bagi para peneliti untuk mempelajari lebih lanjut tentang sejarah media Afghanistan.